Rationality of Empirical Antibiotic Usage among Digestive Surgery Inpatients at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia: Gyssens Criteria Analysis - Yunivita, Vycke; Assyifa, Nanda; Yarman, Indra Prasetya; Bashari, Muhammad Hasan; Satriasih, Tulus (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Many empirical antibiotics are prescribed unnecessarily, contributing to the rise in the incidence of antibiotic resistance. Preventing infection of surgical sites is one of the most frequent purposes of empirical antibiotic usage. Therefore, this study aimed to analyze the rationality of empirical antibiotic usage among digestive surgery inpatients based on the Gyssens criteria and clinical features outcomes.Methods: A descriptive method was used with a cross-sectional design. Data was collected from medical records of patients underwent digestive surgery and had received empirical antibiotic therapy post-surgery from July to September 2021 at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Subsequently, the data was analyzed using the Gyssens method to qualitatively assess the rationality of antibiotic use based on specific criteria, classified from rational (category 0) to various levels of irrational use (categories I-VI). Clinical outcomes were evaluated by assessing leukocyte count, clinical symptoms of fever, and the appearance of surgical site infection before and after administration of empirical antibiotics.Results: In total, 70 empirical antibiotic prescriptions were obtained from 42 patients, with only 40% of patients using rational antibiotics, whereas 60% of antibiotics were used inappropriately (category I-VI). Clinical evaluation showed no fever, edema, or erythema and reduced leukocytosis and exudate/pus post-therapy.Conclusions: Inappropriate empirical antibiotic prescription for digestive surgery inpatients at Dr. Hasan Sadikin General Hospital based on the Gyssens criteria is high. Nonetheless, clinical outcomes showed improvements in infection-related parameters. These results emphasize the importance of stricter adherence to antibiotic stewardship and regular evaluation of empirical antibiotic practices to optimize usage and patient outcomes.